2020
DOI: 10.1056/nejmc2013656
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Anticoagulant and Abnormal Coagulation Tests in Patients with Covid-19

Abstract: To the Editor: Patients with coronavirus disease 2019 have a profound hypercoagulable state, and complicating venous thrombotic events are common. [1][2][3] Abnormalities in coagulation screening measures, including a prolonged activated partial-thromboplastin time (aPTT), have been reported in patients with This finding could be seen as a reason to avoid the use of anticoagulation at both therapeutic and prophylactic doses.A prolonged aPTT may indicate a clottingfactor deficiency or the presence of an inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
472
3
22

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(524 citation statements)
references
References 3 publications
12
472
3
22
Order By: Relevance
“…As far as interpretable and based on available results in previous studies, 5,7‐9 in none of the patients was triple positivity demonstrated. In our patient cohort, only two patients were triple positive, of whom none showed thrombotic complications.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…As far as interpretable and based on available results in previous studies, 5,7‐9 in none of the patients was triple positivity demonstrated. In our patient cohort, only two patients were triple positive, of whom none showed thrombotic complications.…”
Section: Discussionmentioning
confidence: 67%
“…Bowles et al described 35 patients in detail, and detected 91% of 35 patients positive for LAC in a workout for prolonged APTT 8 . Six of 35 patients (18%) were positive in the APTT system only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Reports of lupus-anticoagulant mediated artificial prolongation of the partial thromboplastin time (PTT) in patients with COVID-19 make monitoring of therapeutic anticoagulation using anti-Xa levels ideal. 23 A conservative approach to VTE prophylaxis according to severity of COVID-19 and comorbid disease states is outlined in ►Table 5.…”
Section: Prophylaxis For Venous Thromboembolismmentioning
confidence: 99%
“…Severe COVID-19 is associated with an elevation of in ammatory cytokines, which can increase the expression of tissue factor and the suppression of anticoagulant factors 10 . Recently, lupus anticoagulation has frequently been observed in COVID-19 subjects, and this could also be another possible mechanism of abnormal coagulopathy 11 .…”
Section: Introductionmentioning
confidence: 99%